The Role of Cooperatives and MSMEs in Encouraging Financial Inclusion in Rural Communities - Fina Lubnia Sari; Wilfi Tizka Sari; Mashudi (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting financial inclusion in rural communities. MSMEs have demonstrated resilience during economic crises but still face significant challenges, particularly in terms of capital and marketing. Financial inclusion serves as a solution to improve MSMEs' access to financial services through both conventional and digital institutions. As community-based financial institutions, cooperatives have the advantage of providing inclusive financial services through savings and loans systems, financial education, and mutual economic support. The financial inclusion model implemented by cooperatives not only expands financial access for low-income communities but also strengthens local economic independence. This article analyzes cooperative strategies for enhancing financial accessibility, including their adaptation to financial technology to accelerate MSME financial inclusion. The study findings indicate that strengthening cooperative institutions and integrating them into the national financial system are crucial steps in ensuring the sustainable role of cooperatives and MSMEs in regional economic development.